Value of ultrasound examination of the Leeds Enthesitis Index in assessment of disease activity in psoriatic arthritis - Hamada S Ahmad; Sherief E Farrag; Osama Kombar (Rheumatica Acta: Open Access - Peertechz Publications, 2020)
Background: Enthesitis is a major feature of psoriatic arthritis. However, clinical assessment of enthesitis is known to lack accuracy and have poor interobserver reliability. Objective: This study aimed to determine the added value of the US assessment of enthesitis according to LEI over the clinical assessment in determination of PsA activity. Methods: A total of 75 consecutive PsA patients diagnosed according to Classification Criteria for Psoriatic Arthritis (CASPAR criteria) participated in the study. The LEI score was used to assess the enthesitis. All PsA patients underwent US assessment by the same sonographer who was blinded to the findings of the clinical examination.  Grey scale US imaging was used to assess the longitudinal and transverse planes of the 6 entheseal points of the LEI. Results: Active PsA Patients had a significantly higher inflammation score than the PsA patients with MDA at each of the 6-LEI points. Subsequently, active PsA group has significantly higher total inflammation score than in the PsA group with MDA. On the other hand the total damage score as well as the damage score at the 6-LEI points showed insignificant difference between the two groups. A significant correlation was identified between PASDAS with the LEI score and with the total US inflammation score. However, no significant correlation was found between the PASDAS and the total US damage score. Conclusion: US examination of 6-LEI points is an accurate method to assess entheseal abnormalities and is significantly correlated to disease activity in PsA patients.